Assisted Reproduction and Reproductive Rights - Comparative Aspects between Republic of North Macedonia and Republic of Kosovo - Arta SELMANI; Julinda ELEZI (Prizren Social Science Journal, 2020)
Developments in science and technology have, among other things, challenged the family. Human values, which change in step with this technological progress, have faced many legal, moral and ethical dilemmas which await answers from the science on bioethics. We are in such a situation when we discuss about many advances in contemporary and national family law, including new forms of family reproduction that differ from a natural process of child conceiving. The authors in this paper bring comparative aspects of biomedical and family legislation of the Republic of North Macedonia and Republic of Kosovo. Among other things, they emphasize that given the traditional and biological model of the family in our society, new reproductive forms are a very reserved topic in the family and biomedical field, but it awakens a curiosity of discussions on ethics, philosophy and legal regulation of reproduction of human beings in both countries. The numerous stereotypes that prevail in the society of both countries regarding the application of artificial reproduction technology methods are contrary to many legal and medical justifications for couples who do not have the opportunity to become parents  in a biological (natural) way.